Role of class I histone deacetylases in the regulation of maspin expression in prostate cancer. Issue 8 (11th May 2020) - Shankar, Eswar; Pandey, Mitali; Verma, Shiv; Abbas, Ata; Candamo, Mario; Kanwal, Rajnee; Shukla, Sanjeev; MacLennan, Gregory T.; Gupta, Sanjay
Abstract: Maspin repression is frequently observed in prostate cancer; however, the molecular mechanism(s) causing the loss is not completely understood. Here, we demonstrate that inhibition of class I histone deacetylases (HDACs) mediates re‐expression of maspin which plays an essential role in suppressing proliferation and migration capability in prostate cancer cells. Human prostate cancer LNCaP and DU145 cells treated with HDAC inhibitors, sodium butyrate, and trichostatin A, resulted in maspin re‐expression. Interestingly, an exploration into the molecular mechanisms demonstrates that maspin repression in prostate tumor and human prostate cancer cell lines occurs via epigenetic silencing through an increase in HDAC activity/expression, independent of promoter DNA hypermethylation. Furthermore, transcriptional activation of maspin was accompanied with the suppression of HDAC1 and HDAC8 with significant p53 enrichment at the maspin promoter associated with an increase in histone H3/H4 acetylation. Our results provide evidence of maspin induction as a critical epigenetic event altered by class I HDACs in the restoration of balance to delay proliferation and migration ability of prostate cancer cells.